1990
DOI: 10.1177/019459989010300406
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo and in vitro effect of phenylephrine (neo synephrine) on nasal ciliary beat frequency and mucociliary transport

Abstract: Twenty volunteers with normal noses were studied to determine the effect of phenylephrine on nasal ciliary function. In vivo study of this drug was performed in 15 patients and revealed a significant increase in their ciliary beat frequency from a control of 11 Hz to 12.03 Hz (p = 0.001). Mucociliary transit times in these volunteers were also studied, revealing a mean of 9.9 minutes prestimulation and 10.2 minutes poststimulation, which was not statistically significant (p = 0.77). Five additional subjects do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…3 ). Our results are in agreement with effects of a range of concentrations of phenylephrine, from 0.01 to 0.5%, on human nasal CBF [15] . Since both the absolute ( ϳ 1 Hz) and normalized increments ( ϳ 10%) of CBF were relatively small, an accurate quantification of the ciliary activity with high temporal resolution was required to detect the small change in CBF within 1 min.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…3 ). Our results are in agreement with effects of a range of concentrations of phenylephrine, from 0.01 to 0.5%, on human nasal CBF [15] . Since both the absolute ( ϳ 1 Hz) and normalized increments ( ϳ 10%) of CBF were relatively small, an accurate quantification of the ciliary activity with high temporal resolution was required to detect the small change in CBF within 1 min.…”
Section: Discussionsupporting
confidence: 89%
“…Human nasal CBF decreased significantly in cilia that had been incubated in different concentrations of phenylephrine (from 0.125 to 2.5%) for different periods of time (from hours up to 6 days), even at the lowest concentrations of phenylephrine (0.125%) [10] . Other reports indicate that shorter incubation times (60 min) in lower concentrations of phenylephrine (0.01%) cause a stimulatory effect on human nasal CBF, while higher concentrations (0.25 and 0.5%) cause inhibitory effects [15] . It is well known that effects of nasal decongestants on nasal CBF may influence nasal MTT.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, we demonstrated that the clinically used concentration of ephedrine (0.5%) induced the highest stimulatory effect, without any obvious inhibitory effect on human nasal CBF 25. Phillips and colleagues26 investigated the in vivo and in vitro effect of phenylephrine on nasal CBF and mucociliary transport of healthy volunteers and demonstrated that while phenylephrine had a cilio-stimulatory effect in vivo as well as at a low concentration (0.01%) in vitro , it also had a cilio-inhibitory effect at higher concentrations (0.25% and 0.5%) in vitro 26. Similarly, Min and colleagues27 reported that at concentrations of 0.125% to 2.5%, phenylephrine induced a significant decrease in human nasal CBF in a dose-dependent- and time-dependent manner 27…”
Section: Effects Of Intranasal Decongestantsmentioning
confidence: 66%